Pathway to care among adolescents and young adults with breast cancer in Nigeria: a mixed methods study - Atara Ntekim; Ayorinde Folasire; Oluwaponmile A. Odukoya; Anthonia Sowunmi; Adewunmi Alabi (BMC Cancer)
Abstract Background The mortality from breast cancer (BC) is still high in Nigeria and other low-and medium-income countries (LMICs) especially among adolescents and young adults. This is partly due to late presentation for diagnosis and treatment. It is recommended that to optimize the effectiveness of treatment, the total time which is the interval from symptom onset to initiation of treatment, should be less than 90 days as recommended by the World Health Organization (WHO). The aim of this study was to determine the extent of delays in accessing care and possible reasons for such delays among young adult females with breast cancer in Nigeria. Methods A mixed-method convergent parallel study design was used. The study was conducted at two academic hospitals in southwest Nigeria. Data were collected using a semi-structured assessment tool and an in-depth interview guide. Both the quantitative and qualitative data were collected concurrently. This approach was adopted to aid in the collection of different but complimentary data at the study sites to enrich the interpretation of the results. Results A total of 46 female participants were recruited into the quantitative component of the study, and the mean age was 34.2 ± 4.4 years. Most had higher education, were married, and were in a lower earning bracket. Majority participants had low knowledge of symptoms and signs of breast cancer. As low as 7 (15.2%) patients had the time between symptom discovery and treatment initiation [Total Treatment Time (TT)] within 90 days (median 281.5; range 31-5260). Twenty-seven (58.6%) participants had diagnostic interval within 60 days (median 40 days [Inter Quartile Range (IQR) 7–4745 days]. Most participants interviewed 39 (85%) knew that breast lump was a possible sign of breast cancer while a sizable number 19 (41%) could not name risk factors for breast cancer. Family history was the most recognised risk factor for breast cancer by 21(46%) of participants interviewed. Conclusion Breast health awareness is low among adolescents and young adults with breast cancer in Nigeria, as most participants 33(72%) lacked knowledge of early symptoms and signs of breast cancer. Very few 7(15%) of the participants commenced treatment within the WHO recommended 90 days of noticing breast symptoms. Sixty percent of the participants met the diagnostic interval of within 60 days as against recommended 80%. There is need to intensify the education of young Nigerian females on breast cancer and the importance of breast self-examination.